2006
DOI: 10.1002/esp.1422
|View full text |Cite
|
Sign up to set email alerts
|

Wind erosion of blanket peat during a short period of surface desiccation (North Pennines, Northern England)

Abstract: Strong winds are a characteristic feature of UK upland areas. Despite this, understanding of aeolian processes in upland environments of the UK is limited. This paper presents direct measurements and observations of blanket peat erosion by wind action during a two week period of desiccation in the North Pennines, Northern England. A circular configuration of mass flux sediment samplers was used to collect peat eroded by wind action from 16 cardinal compass directions. Meteorological conditions (wind speed, win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Vieira et al (2004) presented the influence of oblique rainfall on the genesis of coarse sand accumulations and emphasized the importance of RD-WDT as a main transportation mechanism. The importance of the process on blanket peat erosion was signified by Warburton (2003), Evans and Warburton (2005) and Foulds and Warburton (2007a). Foulds and Warburton (2007b) found that dust flux rates by saltation were in general up to two-orders of magnitude lower than that recorded during periods of sustained wet weather.…”
Section: Introductionmentioning
confidence: 99%
“…Vieira et al (2004) presented the influence of oblique rainfall on the genesis of coarse sand accumulations and emphasized the importance of RD-WDT as a main transportation mechanism. The importance of the process on blanket peat erosion was signified by Warburton (2003), Evans and Warburton (2005) and Foulds and Warburton (2007a). Foulds and Warburton (2007b) found that dust flux rates by saltation were in general up to two-orders of magnitude lower than that recorded during periods of sustained wet weather.…”
Section: Introductionmentioning
confidence: 99%
“…Erosion by flowing water is the dominant component in most UK peatlands; but local topography exerts a strong control in determining process dominance (Evans and Warburton, 2007). Bare peat surface microtopography is especially dynamic and patchy; different surface processes leave distinctive topographic roughness signatures and local surface microtopography can adjust rapidly in response to changing processes over relatively short timescales (Foulds and Warburton, 2007). Bare peat surface microtopography is especially dynamic and patchy; different surface processes leave distinctive topographic roughness signatures and local surface microtopography can adjust rapidly in response to changing processes over relatively short timescales (Foulds and Warburton, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are accumulated works performed under controlled laboratory conditions for essentials of WDR erosion processes, field studies and observations are still very rare [79] particularly for the splash-saltation transport process. The reason is that, despite the fact that a certain number of active and passive aeolian sediment traps for wind-driven sediment transport exist, there has been no trap specifically designed to catch and quantify splash-saltating particles during rainfall events accompanied by strong winds previously.…”
Section: Introductionmentioning
confidence: 99%